Comparative study of the inelastic response of base isolated buildings. - Ordonez, Daniel
This article presents a numeric comparative study of the inelastic structural response of base isolated buildings. The comparative study includes the following isolation systems : laminated rubber bearings, New Zealand one, pure friction and the frictional pendulum ones. The study is based on obtaining non-linear response spectra for various design parameters using six earthquake records. Usually the base isolation of a new building seeks to maintain the structure in the linear elastic range. The response of old weak buildings or the response of new ones subjected to extreme earthquakes may not be, necessarily, in the aforementioned ideal elastic range. Consequently, it is important to characterize the response of isolated buildings responding inelastically. A conclusion from this research is that the isolators affect significantly the structural response of weak systems. Rubber isolators seem slightly less sensitive to plastification that may occur in the structure compared to friction isolators. Ductility demands in the structure are affected significantly by friction and neoprene protected systems, in particular sliding ones where larger demands are obtained.
Keywords: Base isolation; Passive control; Sliding isolation; Hysteretic isolation; Friction isolation; Neoprene isolation; Structural strengthening; Earthquake retrofitting